Future robots : towards a robotic science of human beings - Parisi, Domenico (Amsterdam ; Philadelphia : John Benjamins Pub. Company, 2014)
This book is for both robot builders and scientists who study human behaviour and human societies. Scientists do not only collect empirical data but they also formulate theories to explain the data. Theories of human behaviour and human societies are traditionally expressed in words but, today, with the advent of the computer they can also be expressed by constructing computer-based artefacts. If the artefacts do what human beings do, the theory/blueprint that has been used to construct the artefacts explains human behaviour and human societies. Since human beings are primarily bodies, the art.
1. Robots as theories of behaviour -- 2. Robots that have motivations and emotions -- 3. How robots acquire their behaviour -- 5. Robots with a mental life -- 6. Social robots -- 7. Robotic families -- 8. Robots that learn from other robots and develop cultures and technologies -- 9. Robot that own things -- 10. Political robotics -- 11. Robotic economies -- 12. Individually different robots and robots with pathologies -- 13. Robots that have art, religion, philosophy, science, and history -- 14. Human robots are future robots -- 15. How human robots can be useful to human beings.
Print version record.
Includes bibliographical references and index.
English.
Added to collection customer.56279.3
Keywords: Robotics -- Human factors; Androids; Artificial intelligence; Artificial Intelligence; Robotique -- Facteurs humains; Androïdes.; Intelligence artificielle; artificial intelligence; TECHNOLOGY & ENGINEERING -- Engineering (General); Androids; Artificial intelligence; Robotics -- Human factors